Pengaruh Variasi Bentuk Kampuh Las TIG (Tungsten Inert Gas) Terhadap Uji Tarik dan Struktur Mikro Pada Material Plat Stainless Steel 201 - Pratama, Mokhammad Yoga; Mufarida, Nely Ana; Kosjoko, Kosjoko (Journal of Engineering Science and Technology, 2023)
Welding technology has an integral role in the manufacturing technology domain. To create high-quality structures requires technology that allows joining metals. It is in this phase that welding technology comes into play. TIG (Tungsten Inert Gas) welding is a form of tungsten gas arc welding, where the electrode acts as an arc supplier that does not melt during the welding process. The Gas Tungsten Acr Welding technique is generally used more on light metals such as magnesium, aluminum, and stainless steel, and other types of metal. This type 201 carbon steel has several mechanical characteristics, including a tensile strength of 580 Mpa, an elastic limit (yield strength) of 198 Mpa, an elongation rate of 50%, and a hardness of 87 HRBI. The aim of this research is to determine the tensile strength and microstructure of TIG (Tungsten Inert Gas) welding results with 45 degrees of V, U and J seams. This research was carried out with several flat 2D test models of 45 degrees of V, U and J seams with current. 110 - 120. This research was conducted at the Banyuwangi Job Training Center, in the Materials Laboratory for Mechanical Engineering at Sebelas Maret University, Surakarta and at the Mechanical Engineering Laboratory at Jember State University. In this research, the results of changes in tensile strength were quite significant. The lowest tensile strength value is found in the J weld seam with an average value of 394.4 MPA. Meanwhile, the highest tensile strength value is found in the V weld seam with an average value of 531.1 MPA. The results of the microstructure for J seam have the largest phase grains and V seam forms the smallest phase grains compared to the others. Kampuh V has quite a large number of grains because they are relatively small and dense.